Censurae Librorum - Komorowska, Joanna (Polskie Towarzystwo Filologiczne, 2018)
Andrea Falcon (ed.), Brill’s Companion to the Reception of Aristotle in Antiquity, Leiden–Boston: Brill, 2016 (Brill’s Companions to Classical Reception 7), 512 pp., ISBN 978-90-04-26647-6, €182.00.
Keywords: censurae liborum